Sociological Study of the Effect of Social Capital on Women's Social Vitality (Case study: Women in Tehran) - Mahboubeh Zarreh Parvar Tali; Faizollah Nouroozi; Abdolreza Adhami (توسعه اجتماعی)
Happiness, because it is always associated with happiness, optimism, hopes and trust, can be a catalyst, an accelerating role in the development process of a society. The purpose of this research is to investigate the effects of social capital on the social vitality of women in Tehran. Its theoretical framework is integrated and two theories of risk and late modernity of Anthony Giddens and comparison theory are used. The research method is quantitative and descriptive-explanatory and cross-sectional in terms of time. The research technique is a survey and the tool is a questionnaire, using a multi-stage cluster probability sampling method, with a sample size of 384 women living in the city of Tehran, based on the three zoning of the city of Tehran: traditional, modern and in transition. , completed and evaluated. In order to analyze the data, descriptive statistics and inferential statistics and regression analysis tests were used to test the research hypotheses. The findings of the research confirm the existence of a significant relationship between social capital and social vitality with a determination coefficient of 0.233. Women living in the modern area of Tehran have the highest level of social capital. Women living in the traditional area are in the next category and the lowest level is related to the women living in the transition area. In this regard, women living in the modern area of Tehran have the highest level of social vitality. In general, 23.9 percent of the respondents had low level of social cheerfulness, 44.5 percent had average level, and 31.5 percent had high level. The social capital of 21.6 percent of the respondents was low, 46.2 percent was medium, and 31.8 percent was high.